'There's Something Wrong with You': How Young People Choose Abstinence in a Heavy Drinking Culture. (November 2017) - Supski, Sian; Lindsay, Jo
Contemporary universities in Western democracies are renowned for heavy drinking youth cultures. In this context, abstinence is 'accountable' behaviour that requires justification. Some previous research has reported accounts of why young people choose not to drink and the social consequences, but there is limited research on how they achieve abstinence in a heavy drinking culture. Drawing on Heller's notion of choosing oneself and Giddens' concept of reflexive choice making, we show how young non-drinking Australian university students emphasize abstinence as an individual lifestyle choice, show determined strength in their decision not to drink and report eventual acceptance from their peers. The non-drinkers in our research use some similar accounts noted in other research such as 'being sporty' or 'focused on their studies', yet they do not position themselves as part of an alternative subculture such as those in straight edge or religious groups. They choose their abstinent selves both in an existential sense and as an act of everyday self-identity. We argue that the choice of abstinence needs to be viewed as a part of a positive claim to identity, alongside other alternative ways of being for university students.